+0  
 
0
266
1
avatar

g(x)=x/5+1

find g^-1(x)

explain how please

Guest Jun 19, 2017
 #1
avatar+86859 
+2

 

g(x) = x/5 + 1

 

Write as

 

y   = x/5 + 1    subtract 1 from each side

 

y - 1  = x/5     multiply both sides by 5

 

5 ( y - 1)  = x   simplify

 

5y  - 5   =  x        "swap"   x and y

 

5x - 5  = y           for y, write  g-1 (x)

 

5x - 5  =    g-1 (x)

 

 

cool cool cool

CPhill  Jun 19, 2017

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.